2009
DOI: 10.1108/13595474200900004
|View full text |Cite
|
Sign up to set email alerts
|

No One Knows: offenders with learning disabilities and learning difficulties

Abstract: There is a lack of clarity about the prevalence of offenders with learning disabilities and learning difficulties. However, it is clear is that, regardless of actual numbers, many offenders have learning disabilities and learning difficulties that interfere with their ability to cope within the criminal justice system. No One Knows is a UK-wide programme led by the Prison Reform Trust that aims to effect change by exploring and publicising the experiences of people with learning disabilities and learning diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Studies that have screened participants for ID as opposed to making a formal diagnosis have reported much higher rates. The No one knows report suggests that up to 7 per cent of prisoners have an IQ of less than 70 with a further 25 per cent having an IQ of less than 80 (Talbot, 2009;Talbot and Riley, 2007). In terms of substance use as a predictor of offending and going to prison, Klimecki et al, (1994) found that 45.1 per cent of first offenders with ID had a history of substance use, rising to 87.5 per cent by the fourth offence suggesting a link to repeat offending.…”
Section: Id and Substance Usementioning
confidence: 99%
“…Studies that have screened participants for ID as opposed to making a formal diagnosis have reported much higher rates. The No one knows report suggests that up to 7 per cent of prisoners have an IQ of less than 70 with a further 25 per cent having an IQ of less than 80 (Talbot, 2009;Talbot and Riley, 2007). In terms of substance use as a predictor of offending and going to prison, Klimecki et al, (1994) found that 45.1 per cent of first offenders with ID had a history of substance use, rising to 87.5 per cent by the fourth offence suggesting a link to repeat offending.…”
Section: Id and Substance Usementioning
confidence: 99%
“…Appropriate adults are not used consistently, and will be sourced only if the LD is made known to police (Leggett et al, 2007;DoH, 2009a). The Prison Reform Trust's focus groups with offenders with LD revealed confusion over who the appropriate adult was, while another study demonstrated that most participants could not see the usefulness of this person, as they "said and did nothing" (Talbot and Riley, 2007;Leggett et al, 2007, p. 170).…”
Section: Introductionmentioning
confidence: 99%
“…There are some programmes for people with lower IQs, with more being developed (HMI Probation, 2015). Community orders can also be unsuitable, as people with LD are significantly less able to follow the rules and keep appointments than others, and unwittingly missing appointments may result in returning to prison (Mason and Murphy, 2002;Talbot and Riley, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition there may be third variables, such as poverty or other family adversity that may increase rates of both criminal behavior and disabilities (White & Loeber, 2008). People with disability face several challenges within the judicial system (Holland, Clare, & Mukhopadhyay, 2002; Talbot, & Riley, 2007). The under-identification of disability is common in judicial systems worldwide (Wertlieb, 1991).…”
Section: Introductionmentioning
confidence: 99%